A study on awareness on allergic disorders and allergen immunotherapy among medical practitioners - Gowda, Giriyanna; S., Pruthvi; Phaneendra, M. S.; Nagaraj, Chitra (International Journal Of Community Medicine And Public Health, 2021)
Background: Allergy is a common ailment affecting more than 20% of the population worldwide. Allergic patients suffer from a debilitating disease with a major impact on their quality of life, work and school performance. Allergic disorders can be debilitating, with a major impact on their quality of life, work and school performance. AIT (Allergen immunotherapy), modify the natural history of allergic disease and prevent the progression of allergic respiratory diseases by maintaining a long-lasting effect. Since the awareness among medical practitioners plays very important role in advising AIT for allergy patients, we attempted to conduct this study. Methods: This was a descriptive study done for a period of three months from December 2016 to February 2017. The 110 study subjects were recruited through purposive sampling. Doctors of various specialties and general practitioners were interviewed using self-administered, semi-structured questionnaire. Results: There were 73 (66.36%) males and 37 (33.64%) females. Mean age of the medical practitioners was 35.73±13.07 (Mean±SD). 98 (89.09%) of the practitioners were aware of skin prick test for the diagnosis of allergy, 70 (63.3%) subjects had heard term AIT, 59 (84.28%) were aware about subcutaneous immunotherapy (SCIT) and 25 (35.71%) of sublingual immunotherapy (SLIT). Forty-four (62.96%) were not advising immunotherapy for their patients in spite of having awareness on immunotherapy. The common reasons for not advising immunotherapy were long duration of treatment, high cost, less effective, not available in India, fear of side effects and others. Conclusions: Though the awareness among medical practitioners on AIT was good, majority are not advising because of long duration of treatment, high cost, less effective, not available in India, fear of side effects and others.